This is not about women: “Same Old West” - Ferreira, Alana de Oliveira; Pedroni, Fabiana (Farol, 2025)
This article critically analyzes the dynamics of hegemonic masculinity in the film "Same Old West" (2024), connecting them with debates on necropolitics (Mbembe), necrobiopower (Bento), and gender decolonization (Preciado). It demonstrates how male violence operates as a self-destructive ritual in the face of an inability to process emotions and sustains micro-sovereignties over life and death. Blaming women for male suffering is identified as a structuring axis, linked to anti-gender discourses that idealize a patriarchal past. We conclude that the film exposes the crisis of masculinity as a necropolitical phenomenon, in light of which we can propose the deconstruction of binaries and the adoption of dissident epistemologies to overcome gender hierarchies.